Superfícies mínimas nos espaços Damek-Ricci lorentzianos 4-dimensionais - Silva, Railane Antonia da (2019)
In this work, we will detail the study of the Lie Group equipped with a left invariant Lorentzian metric called Damek-Ricci space. Based on the results obtained by Adriana A. Cintra, Francesco Mercuri and Irene I. Onnis in "Minimal surfaces in Lorentzian Heisenberg group and Damek–Ricci spaces via the Weierstrass representation"[5], we present the construction of the formula of representation of Weierstrass, as well as some examples of conformal minimal immersions, for the case where these spaces are 4-dimensional Lorentzian.